2002
DOI: 10.1128/jcm.40.11.4172-4179.2002
|View full text |Cite
|
Sign up to set email alerts
|

Single and Combination Antibiotic Susceptibilities of Planktonic, Adherent, and Biofilm-Grown Pseudomonas aeruginosa Isolates Cultured from Sputa of Adults with Cystic Fibrosis

Abstract: Evidence suggests that Pseudomonas aeruginosa bacteria form biofilms within the airways of adults with cystic fibrosis (CF). The objective of this study was to determine whether clinical isolates of P. aeruginosa recovered from adults with CF have similar susceptibilities to individual antibiotics and to antibiotic combinations when grown as adherent monolayers or as biofilms compared to when they are grown using planktonic methods. Twelve multiresistant P. aeruginosa isolates, one mucoid and one nonmucoid fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
101
0
2

Year Published

2004
2004
2016
2016

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 133 publications
(108 citation statements)
references
References 34 publications
5
101
0
2
Order By: Relevance
“…Since antibiotics have greater bactericidal efficacy against planktonic bacteria than biofilm [1,7,40], the combination of C2DA with traditional antibiotics could have improved bactericidal efficacy and infection prevention therapies [16]. The combination of daptomycin or vancomycin with C2DA slightly enhanced the antibiofilm effects, but the combination of linezolid resulted in biofilm inhibition at concentrations two to 16 times lower than for either antimicrobial alone.…”
Section: Discussionmentioning
confidence: 99%
“…Since antibiotics have greater bactericidal efficacy against planktonic bacteria than biofilm [1,7,40], the combination of C2DA with traditional antibiotics could have improved bactericidal efficacy and infection prevention therapies [16]. The combination of daptomycin or vancomycin with C2DA slightly enhanced the antibiofilm effects, but the combination of linezolid resulted in biofilm inhibition at concentrations two to 16 times lower than for either antimicrobial alone.…”
Section: Discussionmentioning
confidence: 99%
“…Single and combination antibiotic susceptibility testing of P. aeruginosa, grown as biofilms, has been previously validated and shown to be reproducible [7,21].…”
Section: Biofilm Testingmentioning
confidence: 99%
“…A rocking table was used to produce shear forces across each peg, resulting in the formation of equivalent biofilms at each peg site. The current authors have previously shown by electron microscopy that this method results in biofilm growth on the pegs [7]. The biofilm culture was then transferred to a standard 96-well plate in which dilutions of antibiotics had been prepared and then incubated overnight at 35uC in ambient air.…”
Section: Biofilm Testingmentioning
confidence: 99%
See 1 more Smart Citation
“…In other words, alternative mechanisms must have been operational in the clustered strain to lead to mucoidy [20]. Multiple and diverse bacterial factors associated with the ability of cross-infecting P. aeruginosa strains to successfully establish persistent infection in other hosts are conceivable including: an improved ability to aerosolise [9]; a propensity to infect sheltered extrapulmonary sites [21] or adhere to CF mucosal surfaces [22]; a better ability to prosper in the abnormally anaerobic environment of the airway surface liquid typical of older CF patients; an increased tendency to form biofilms in the respiratory tract; or increased intrinsic antibiotic resistance [3] (in turn related to the propensity to form biofilms) [23]. Further work is required to better define these bacterium-specific factors.…”
Section: Discussionmentioning
confidence: 99%